Himasthla escamosa n. sp. (Digenea: Echinostomatidae) from the Kelp Gull, Larus dominicanus (Charadriiformes: Laridae) on the Patagonian coast, Argentina - Diaz, Julia Inés (2004)
In this paper, we describe a new species of Himasthla Dietz, 1909 (Digenea: Echinostomatidae) from Larus dominicanus Lichtenstein (Aves: Laridae) in northern Patagonia, Argentina. We also provide the hosts, localities, and key diagnostic features and measurements of the, so far, 25 described species. From these species, H. militaris, H. leptosoma, H. elongata, H. secunda, H. megacotyla, H. multilecithosa, H. piscicola, H. compacta, H. schachtachtinskoi, H. littorinae, H. continua, H. avosettae, and H. interrupta are similar to H. escamosa n. sp. in having 29 head collar spines. Himasthla leptosoma, H. piscicola, H. multilecithosa, H. interrupta, H. continua, and H. militaris can be mainly differentiated from the new species by the extension of its vitellaria. Himasthla avosettae, H. megacotyla, H. elongata, H. compacta, and H. littorinae have a different size and/or arrangement of head collar spines than H. escamosa. H. secunda can be distinguished from H. escamosa n. sp. in having larger body, testes, and ovary, and a different position of the ovary. The comparison with H. schachtachtinskoi could not be done because the bibliography was not available. This is the first record of the genus in Argentina and for L. dominicanus.